Radiation security of the far east: problems and solutions - Tananaev, Ivan G.; Avramenko, Valentin A. (Journal of the Belarusian State University. Ecology, 2018)
The Far East is an outpost of the Russian Federation in the Asia-Pacific region, the main modern priorities of which are the development of the industrial and economic and social and economic activities of the region in terms of developing raw materials, creating new jobs and increasing population in safe and comfortable environments, and radiation safety. Scientists from FEFU and FEB RAS, through systematic studies and practical developments, provided scientific support for the final disposal of accumulated LRW, treatment and rehabilitation of natural objects contaminated with radionuclides and toxic elements, which helped to eliminate the potential threat of ecological and technogenic accidents in the Far East. New magnetic materials based on highly porous natural mineral-like carriers, resorcinol-formaldehyde resins, quantitatively extracting dangerous radionuclides from sea water, have been synthesized and introduced. A technology with an active hydrodynamic regime for processing LRW containing sea water and oil products has been developed. Experimental-industrial plants for the production of sorption-reagent materials, for the utilization of complex LRW are being set up at JSC «DVZ «Zvezda». Thus, having overcome nuclear legacy in Primorye, scientists from FEFU and FEB RAS managed to ensure radiation safety at enterprises using atomic energy.